DESKRIPSI KETERAMPILAN PSIKOMOTORIK SISWA KELAS XI IPA SMAN 8 PONTIANAK PADA PRAKTIKUM TITRASI ASAM BASA - Holly, Desi Natalia; Sahputra, Rachmat; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract                                                                                                                                The aim of this study was to describe psychomotor skill of students in acid-base titration practicum. The subjects of this study were students of  class XI IPA 1 in academic year 2017/2018 consisting of 40 students. The form of this research was a descriptive study. The data were collected through direct observation and direct communication technique. The research procedure consists of the preparation, implementation and final stages. Preparation stage consist of direct observation, problem identification, problem formulation, proposal preparation, designing research instruments in the form of practicum observation sheets and LKS, instrument validation, and instrument revisions. Implementation stage consist of acid-base titration practicum and psychomotor skills assessment. Final stage consist of calculating the total psychomotor skills score of students, changing the score into the expected percentage, determining the category of students psychomotor skills, conducting interviews to find students problems during the practicum, describing students psychomotor skills. Based on the results of psychomotor analysis in acid-base titration practicum, the average psychomotor skills of students were 85.6% which was categorized as very good.  Keywords: Psychomotor skills, titration, acid-base